Digital natives: the engagement experience to online protection. Issue 2 (19th June 2017) - Recalde, Monica; Gutiérrez-García, Elena
Abstract : Purpose: This study aims to center on understanding how stakeholder engagement processes improve online child protection in telecom companies. The literature review and findings shed light on the management of networks to identify, prevent and mitigate the adverse impacts of information and communication technologies (ICTs)[1] and to find opportunities in terms of new policies and services development. Design/methodology/approach: Three multinational telecom companies were analyzed with a qualitative focus combining three research tools: the analysis of 81 corporate reports, self-administered questionnaires and semi-structured interviews. Findings: Firms establish a collaborative network with a large number of stakeholders such as public authorities, non-governmental organizations, educational institutions, representatives of families and expert researchers. The outcomes of these networks range from the development of new products and services (filters, child safety software and protection apps) to the co-creation of new corporate policies with a high social impact (self-regulation, sectorial codes, awareness initiatives and reporting). Practical implications: This study outlines guidelines for the industry in identifying, engaging and making decisions in a collaborative way when managers have to engage with multiple stakeholders regarding child protection. The academic debate and the empirical findings have many practical implications for ICT companies whose users are children and teenagers. Originality/value: Despite its significance, stakeholder management is underexplored in the literature of protection for young people. The academic field and the professional arena appear to have little to say regarding how executives manage engagement processes.